REPRESENTASI KORBAN KEKERASAN SEKSUAL PADA FILM MARLINA SI PEMBUNUH DALAM EMPAT BABAK - Tubagus Muhammad Rizky Kusumawardana; Ilham Gemiharto; Evi Rosfiantika (Jurnal Komunikasi & Media Digital, 2024)
Marlina the Murderer in Four Rounds is a movie released in Indonesia in 2017. Directed by Mouly Surya, this film became one of those that received a lot of attention at various international film festivals. The movie tells the story of a young widow who is left in the interior of the Indonesian island of Sumba. One night, a group of criminals come to her house to seize her property and rape her. This movie is not only about Marlina's struggle against oppressors and injustice but also about women's empowerment in the face of difficult and harsh situations. This research aims to find out the meaning of denotation, connotation, and myth that represent sexual violence from the perspective of fashion. The research method used in this study utilizes Roland Barthes' semiotic analysis in examining the nonverbal messages of fashion. The results of the research show that in the movie Marlina the Killer in Four Rounds denotatively, acts of sexual violence experienced by women cause loss and suffering; connotatively, victims of sexual violence are powerless against the perpetrators; and mythically sexual violence often occurs in the closest relationships, namely dating and households. Not only that, sexual violence occurs when there are many people in the victim's house.